(untitled) (The Research of Medical Science Review, 2024)
Objective: To determine the frequency of oral precancerous lesions among patients presenting with recurrent aphthous ulcer. Methodology: This study was carried out at the Department of Otorhinolaryngology and Head & Neck Surgery, Dr. Ruth K.M. Pfau Civil Hospital, Karachi, in 2024. A total of 120 patients were recruited through non-probability consecutive sampling after taken written informed consent. This study included patients aged 15–60 years, of either gender, presenting with recurrent aphthous ulcers (RAU). Patients underwent an oral inspection for oral precancerous lesions, defined clinically by appearance as white, red, or mixed mucosal manifestations. The data was analysed using SPSS 26.0. The Chi-square test was used to compare patients with and without oral precancerous lesions. A P value of < 0.05 was considered significant. Results: The mean age of the participants is 41.60 ± 15.58 years, ranging from 16 to 68 years. The study sample consists of 75% males and 25% females. Out of the total sample, oral precancerous lesions were noted in 31 (25.83%) and 89 (74.17%) do not. In the OPL group, 6.5% were non-smokers and 93.5% were smokers, compared to 44.9% and 55.1%, respectively, in the No OPL group with statistically significant difference was noted (p = 0.0001). Among betel nut chewers, 87.1% had OPL, compared to 41.6% in the No OPL group. For non-chewers, 12.9% were in the OPL group versus 58.4% in the No OPL group, indicating a significant association between betel nut chewing and OPL (p = 0.0001). Conclusion: This study highlights an important and significant relationship of betel nut, and smoking status with oral precancerous lesions. Preventive measures in the form of public awareness, screening, and cessation are required to reduce the incidence and progression of these lesions into malignancy. Further research should validate the long-term outcomes and causality in higher-risk populations.